MAXIMIZE DIGITAL GAME BASED LEARNING TO TEACH ENGLISH FOR YOUNG LEARNERS: TEACHER’S VIEW - Zen, Aida Fitrianah; Rinda (Universitas Al-Qolam Malang, 2024)
Digital Game-Based Learning (DGBL) has gained significant popularity in Teaching English to Young Learners (TEYL) due to its potential to enhance student engagement and motivation. This article explores the teacher's view of the use of DGBL in TEYL. Several areas of the study such the different of conventional and digtal game for teaching EYL, lesson plan, and the use of Agenda web and duolingo as the digital platform in teaching DGBL obtained from the deepper interview. Support for future research are suggest in the conclusion. Keywords: DGBL, TEYL, Teacher’s view